Radiological evaluation of long term complications of oral rehabilitations of thin ridges with titanium blade implants - P. Diotallevi; L. Dal Carlo; M.E. Pasqualini; S. Mazziotti; M. Nardone; E. Moglioni (Ariesdue, 2014)
Aim: The aim of this study was to assess the sensitivity of orthopantomography (OPT) in the diagnosis of long term complications in oral rehabilitations with blade implants. Materials and methods A total of 235 blade implants in 189 patients, inserted between 1988 and 2003, were retrospectively analyzed. The records consisted of a first OPT taken between January and December 2010, and a second one 12 months after. The evaluation of implant health considered: integrity of the blade, normal radiological representation of the bone around the implant, dense and cortical appearance of bone around the implant collar. The evaluation of radiological complications considered: implant fracture, bone resorption around the implant, recession of the bone around the implant collar. Results The sensitivity of the panoramic evaluation was equal to 100%. The complications detected were 5 cases of periimplantitis, 9 cases of bone pericervical bone recession and 3 cases of fracture of the implant body. In cases of pericervical bone resorption the following radiological check up 12 months after the first one showed the progression of the disease in 6 out of 9 cases, with irreversible implant failure. In subjects with a radiological pattern of implant health there were no complications in the subsequent check up after 12 months. In the subjects with complications the specificity was equal to 100%. Conclusion The radiographic evaluation by the means of OPT has shown high sensitivity in the diagnosis of long term complications of oral rehabilitations with blade implants and allows prompt therapeutic interventions. Radiological complications appeared mostly in the long term check ups and mainly consisted in recession of the bone around the neck or around the entire implant. More rarely implant fractures occurred, which, in the case of blades, sometimes were not associated with any clinical symptoms: therefore, postsurgical evaluation should not be separated from diagnostic imaging.